Method for connecting graphite and transparent material by using ultrafast laser
Through ultrafast laser connection method to transparent materials, the difficulty and stress problems of graphite and transparent materials in the prior art are solved, and the connection effect of large size and lightweight is achieved, which is suitable for the production needs of equipment such as fast reflectors.
Patent Information
- Application Number
- CN202411799160.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art is difficult to achieve effective connection between graphite and transparent materials, especially in the connection of large-sized components, which are troublesome by difficult connection and stress problems, and cannot meet the production needs of "large-size and lightweight".
The method of connecting graphite and transparent materials is adopted to pretreat the surface to be connected between graphite and transparent materials, add acetone or anhydrous ethanol and clamp it, so that the gap between the surface to be welded is free of bubbles, and then connect it with femtosecond or picosecond laser, adjust the laser focus and set the connection parameters to achieve local fusion.
It realizes reliable connection between graphite and transparent materials, avoids joint stress problems, meets lightweight production needs, does not destroy the light transmittance of transparent materials, is suitable for the connection of large-sized components, and is carried out in a room temperature environment, saving energy and easy operation.
Smart Images

Figure CN119613138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for connecting graphite and a transparent material. Background Art
[0002] With the rapid development of aerospace science and space technology in my country, key space optical equipment such as fast reflectors have put forward the production requirements of "large size and light weight". Transparent materials such as glass and transparent ceramics are ideal materials for optical lenses due to their good light transmittance and stable chemical properties. Graphite has low density, light weight, high temperature resistance and corrosion resistance, making it an ideal material for auxiliary structures such as brackets. Therefore, achieving the connection between graphite and transparent materials is the prerequisite for giving full play to the performance advantages of both, and has great potential utilization value in the fields of space optics, astronomy, etc.
[0003] For the connection between graphite and transparent materials, among the existing methods at home and abroad, mechanical connection does not meet the "lightweight" production requirements. The surface activity of materials such as graphite, glass, and transparent ceramics is poor, and they are not suitable for gluing and diffusion welding. Transparent materials may lose their light transmittance after melting and solidifying again, so fusion welding is not suitable for the connection between graphite and transparent material systems. Since transparent materials such as glass and transparent ceramics have stable chemical properties and are difficult to undergo metallurgical reactions, the brazing of graphite and transparent materials requires the addition of active elements, which in turn increases the welding temperature, resulting in greater stress in the brazed joints, especially for the connection of large-sized components. The stress problem is more significant, so the brazing of graphite and transparent materials is basically impossible to achieve, and the "large size and lightweight" production requirements of optical equipment cannot be met. Therefore, the connection of graphite and transparent materials is more difficult. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that it is difficult to connect graphite and transparent materials and it is impossible to achieve large size and light weight, and to propose a method for connecting graphite and transparent materials using ultrafast laser.
[0005] The method of connecting graphite and transparent material by ultrafast laser is carried out in the following steps:
[0006] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0007] Step 2: Add acetone or anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the acetone or anhydrous ethanol fills the gap between the graphite and transparent material surfaces to be welded without bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0008] The ultrafast laser is a femtosecond laser or a picosecond laser;
[0009] Step 3: Adjust the focus of the ultrafast laser and the interface to have a defocus of -50μm to +50μm;
[0010] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0011] The connection parameters include wavelength, pulse width, beam type, spot diameter, repetition frequency, laser power, scanning speed, number of scans, scanning path, scanning line spacing and scanning area.
[0012] Beneficial effects of the present invention:
[0013] 1. Using ultrafast laser to connect graphite and transparent materials, graphite and transparent materials are connected and used in devices such as fast reflectors. This is the first time proposed in this application and is original.
[0014] 2. The present invention uses ultrafast laser to connect graphite and transparent materials without adding auxiliary materials such as bolts and intermediate layers, which meets the lightweight production requirements and does not destroy the light transmittance of the transparent material.
[0015] 3. The present invention can realize reliable connection between graphite and transparent materials because ultrafast laser is an ultrashort pulse laser with extremely high instantaneous power. Ultrafast laser is focused on the interface between graphite and transparent material, and the energy density near the focus will exceed the ablation threshold of the material, causing the material to be ionized and plasma to be generated. The plasma heats the nearby material and melts it, finally realizing partial fusion of graphite and transparent material.
[0016] 4. The present invention can avoid stress problems at the joints between graphite and transparent materials. This is because the average power and heat input of ultrafast lasers are extremely small, and local heating is performed. Therefore, neither graphite nor transparent materials have overall expansion and contraction, thus avoiding stress problems caused by differences in thermal expansion coefficients. Therefore, compared to brazing, the present invention is suitable for connecting large-size components and meets the production needs of large-size components.
[0017] 5. The present invention effectively connects graphite and transparent materials in room temperature and air atmosphere, does not require a high temperature environment, does not require the application of additional loads, etc., saves energy, is simple to operate, has a fast connection speed, and has a high connection efficiency.
[0018] 6. The present invention connects graphite and transparent materials with huge differences in physical and chemical properties, and the shear strength of the joint can reach 8.3 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a photo of the joint interface structure obtained in Example 1;
[0020] Figure 2This is the element surface distribution diagram of the joint obtained in Example 1. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0022] Specific implementation method 1: In this implementation method, the method of connecting graphite and transparent materials using ultrafast laser is carried out in the following steps:
[0023] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0024] Step 2: Add acetone or anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the acetone or anhydrous ethanol fills the gap between the graphite and transparent material surfaces to be welded without bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0025] The ultrafast laser is a femtosecond laser or a picosecond laser;
[0026] Step 3: Adjust the focus of the ultrafast laser and the interface to have a defocus of -50μm to +50μm;
[0027] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0028] The connection parameters include wavelength, pulse width, beam type, spot diameter, repetition frequency, laser power, scanning speed, number of scans, scanning path, scanning line spacing and scanning area.
[0029] Beneficial effects of this embodiment:
[0030] 1. Using ultrafast laser to connect graphite and transparent materials, graphite and transparent materials are connected and used in devices such as fast reflectors. This is the first time proposed in this application and is original.
[0031] 2. This embodiment uses ultrafast laser to connect graphite and transparent materials without adding auxiliary materials such as bolts and intermediate layers, which meets the lightweight production requirements and does not destroy the light transmittance of the transparent material.
[0032] 3. This embodiment can achieve reliable connection between graphite and transparent materials because ultrafast laser is an ultrashort pulse laser with extremely high instantaneous power. The ultrafast laser is focused on the interface between graphite and transparent materials, and the energy density near the focus will exceed the ablation threshold of the material, causing the material to be ionized and plasma to be generated. The plasma heats the nearby materials and melts them, ultimately achieving local fusion of graphite and transparent materials.
[0033] 4. This embodiment can avoid stress problems at the joints between graphite and transparent materials because the average power and heat input of the ultrafast laser are extremely small, and local heating is performed. Therefore, neither the graphite nor the transparent material has overall expansion and contraction, thus avoiding stress problems caused by differences in thermal expansion coefficients. Therefore, compared to brazing, this embodiment is suitable for the connection of large-size components and meets the production requirements of large-size components.
[0034] 5. This embodiment effectively connects graphite and transparent materials in room temperature and air atmosphere, without the need for high temperature environment and the need to apply additional loads, etc., thus saving energy, being simple to operate, having fast connection speed and high connection efficiency.
[0035] 6. This embodiment connects graphite and transparent materials with huge differences in physical and chemical properties, and the shear strength of the joint can reach 8.3 MPa.
[0036] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the transparent material in step 1 is transparent glass or transparent ceramic.
[0037] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the transparent glass described in step one is quartz glass, silica glass, microcrystalline glass, soda-lime glass, aluminosilicate glass or borosilicate glass.
[0038] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the transparent ceramic described in step 1 is an oxide transparent ceramic or a non-oxide transparent ceramic.
[0039] Specific implementation mode five: This implementation mode is different from any one of specific implementation modes one to four in that: the oxide transparent ceramic in step one is sapphire, aluminum oxide, magnesium oxide, beryllium oxide, yttrium oxide or spinel.
[0040] Specific implementation example 6: This implementation example is different from any one of specific implementation examples 1 to 5 in that: the non-oxide transparent ceramic in step 1 is gallium arsenide, zinc sulfide, zinc selenide, magnesium fluoride, calcium fluoride or magnesium aluminate.
[0041] Specific implementation method seven: This implementation method is different from any one of specific implementation methods one to six in that: in step one, the method for polishing the graphite surface to be connected is: polishing step by step using 3000-7000 mesh sandpaper; the method for polishing the transparent material is: polishing step by step using 400-7000 mesh sandpaper.
[0042] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the polishing method of the graphite and transparent material in step one is: using a diamond polishing agent with a particle size of 0.5 to 2.5 μm, polishing for 2 to 20 minutes.
[0043] Specific embodiment nine: This embodiment differs from any one of specific embodiments one to eight in that: the cleaning method described in step one is: first rinse the polished surface with acetone or anhydrous ethanol, then place it in acetone or anhydrous ethanol for ultrasonic cleaning for 5 to 30 minutes, and finally air-dry.
[0044] Specific embodiment ten: This embodiment differs from any of specific embodiments one to nine in that: the wavelength described in step three is in the infrared band, the pulse width is 1fs to 10ps, the beam type is a Gaussian beam, the spot diameter is 1 to 50μm, the repetition frequency is 1kHz to 1MHz, the laser power is 5mW to 50W, the scanning speed is 0.1 to 10mm / s, the number of scans is 1 to 10, the scanning path is Z-shaped, S-shaped, parallel line-shaped, cross-shaped, concentric rectangle, concentric circle or spiral line-shaped, the scanning line spacing is 10μm to 1mm, and the scanning area is in the contact area between graphite and the transparent material.
[0045] Example 1
[0046] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0047] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0048] The transparent material is quartz glass;
[0049] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0050] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0051] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the quartz glass on both sides for 5 minutes;
[0052] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0053] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0054] The ultrafast laser is a femtosecond laser;
[0055] Step 3: Adjust the focus of the ultrafast laser to a defocus amount of 0 μm between the focus and the interface;
[0056] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0057] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 600mW, scanning speed of 0.5mm / s, number of scans of 1 time, scanning path of parallel lines, scanning line (parallel line) spacing of 30μm, and scanning area of 3×3 square in the contact area between graphite and transparent material.
[0058] Figure 1 This is a photo of the joint interface structure obtained in Example 1. Figure 1 As shown, at the position of laser irradiation, graphite and quartz glass are fused, the fusion zone is composed of many particles, and the entire joint has no defects such as pores and cracks. The gap between graphite and quartz glass is almost invisible, indicating that the method of this embodiment and the clamping method can control the gap between the surfaces to be welded very well. Figure 2 : is the element surface distribution diagram of the joint obtained in Example 1. Figure 2 As shown, at the position of laser irradiation, the fusion zone of graphite and quartz glass contains only C and Si elements, indicating that the two undergo metallurgical reaction at high temperature to generate SiC. During the solidification process, chemical bonds are formed between graphite and the fusion zone, and between the fusion zone and the quartz glass, and finally the effective connection between graphite and quartz glass is achieved. According to the test, the shear strength of the joint between graphite and quartz glass in this embodiment is 8.3MPa. For graphite and quartz glass, two materials with huge differences in physical and chemical properties, this embodiment can achieve reliable connection between the two.
[0059] Example 2
[0060] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0061] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0062] The transparent material is glass-ceramics;
[0063] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0064] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0065] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the microcrystalline glass on both sides for 5 minutes;
[0066] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0067] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0068] The ultrafast laser is a femtosecond laser;
[0069] Step 3: Adjust the focus of the ultrafast laser to a defocus amount of 0 μm between the focus and the interface;
[0070] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0071] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 600mW, scanning speed of 0.5mm / s, number of scans of 1 time, scanning path of parallel lines, scanning line (parallel line) spacing of 30μm, and scanning area of 3×3 square in the contact area between graphite and transparent material.
[0072] After testing, it was found that the graphite and the glass-ceramics in this embodiment were well combined, and the shear strength of the joint between the graphite and the glass-ceramics was 6.1 MPa.
[0073] Example 3
[0074] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0075] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0076] The transparent material is quartz glass;
[0077] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0078] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0079] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the quartz glass on both sides for 5 minutes;
[0080] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0081] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0082] The ultrafast laser is a femtosecond laser;
[0083] Step 3: Adjust the focus of the ultrafast laser to a defocus of -25 μm between the interface and the laser beam;
[0084] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0085] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 600mW, scanning speed of 0.5mm / s, number of scans of 1 time, scanning path of parallel lines, scanning line (parallel line) spacing of 30μm, and scanning area of 3×3 square in the contact area between graphite and transparent material.
[0086] After testing, it was found that the graphite and the quartz glass in this embodiment were well combined, and the shear strength of the joint between the graphite and the quartz glass was 7.5 MPa.
[0087] Example 4
[0088] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0089] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0090] The transparent material is quartz glass;
[0091] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0092] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0093] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the quartz glass on both sides for 5 minutes;
[0094] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0095] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0096] The ultrafast laser is a femtosecond laser;
[0097] Step 3: Adjust the focus of the ultrafast laser to a defocus amount of 0 μm between the focus and the interface;
[0098] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0099] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 400mW, scanning speed of 0.25mm / s, number of scans of 1 time, scanning path of parallel lines, scanning line (parallel line) spacing of 30μm, and scanning area of 3×3 square in the contact area between graphite and transparent material.
[0100] After testing, it was found that the graphite and the quartz glass in this embodiment were well combined, and the shear strength of the joint between the graphite and the quartz glass was 8.0 MPa.
[0101] Example 5
[0102] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0103] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0104] The transparent material is quartz glass;
[0105] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0106] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0107] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the quartz glass on both sides for 5 minutes;
[0108] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0109] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0110] The ultrafast laser is a femtosecond laser;
[0111] Step 3: Adjust the focus of the ultrafast laser to a defocus amount of 0 μm between the focus and the interface;
[0112] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0113] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 1W, scanning speed of 1mm / s, number of scans of 1 time, scanning path of parallel lines, scanning line (parallel line) spacing of 30μm, and scanning area of 3×3 square in the contact area between graphite and transparent material.
[0114] After testing, it was found that the graphite and quartz glass in this embodiment were well combined, and the shear strength of the joint between the graphite and quartz glass was 5.9 MPa.
[0115] Example 6
[0116] The method of connecting graphite and transparent material using ultrafast laser in this embodiment is carried out in the following steps:
[0117] Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials;
[0118] The transparent material is quartz glass;
[0119] The grinding method of the graphite surface to be connected is: grinding step by step with 3000 mesh and 7000 mesh sandpaper;
[0120] The polishing method of the transparent material is: polishing step by step using 400 mesh, 800 mesh, 1500 mesh, 3000 mesh, and 7000 mesh sandpaper;
[0121] The polishing method of the graphite and the transparent material is: using a diamond polishing agent with a particle size of 0.5 μm on a polishing cloth, polishing the graphite on one side for 2 minutes, and polishing the quartz glass on both sides for 5 minutes;
[0122] The cleaning method is: first rinse the polished surface with anhydrous ethanol, then ultrasonically clean it in anhydrous ethanol for 5 minutes, and finally air dry it;
[0123] Step 2: Add anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the anhydrous ethanol fills the gap between the surfaces of graphite and transparent material to be welded and there are no bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser;
[0124] The ultrafast laser is a femtosecond laser;
[0125] Step 3: Adjust the focus of the ultrafast laser to a defocus amount of 0 μm between the focus and the interface;
[0126] Step 4: Set the connection parameters and connect the graphite and transparent materials.
[0127] The connection parameters include: wavelength of 1030nm, pulse width of 300fs, beam type of Gaussian beam, spot diameter of 10μm, repetition frequency of 100kHz, laser power of 600mW, scanning speed of 0.5mm / s, number of scans of 1 time, scanning path of concentric circles, scanning line (concentric circle) spacing of 30μm, and scanning area of a circle with a diameter of 4 in the contact area between graphite and transparent material.
[0128] According to the test, the graphite and the quartz glass in this embodiment are well combined, and the shear strength of the joint between the graphite and the quartz glass is 7.3 MPa.
Claims
1. A method for connecting graphite and transparent materials using ultrafast laser, characterized in that: The method of joining graphite and transparent materials using ultrafast lasers is carried out in the following steps: Step 1: Pretreatment of graphite and transparent materials: Grind and polish the surface of graphite to be connected, grind and polish both sides of transparent materials, and then clean the graphite and transparent materials; Step 2: Add acetone or anhydrous ethanol to the surface of graphite to be welded, then place a transparent material and clamp it with a fixture, so that the acetone or anhydrous ethanol fills the gap between the graphite and transparent material surfaces to be welded without bubbles inside, to obtain the parts to be connected, and then place the parts to be connected on the stage of the ultrafast laser; The ultrafast laser is a femtosecond laser or a picosecond laser; Step 3: Adjust the focus of the ultrafast laser and the interface to have a defocus of -50μm to +50μm; Step 4: Set the connection parameters and connect the graphite and transparent materials. The connection parameters include wavelength, pulse width, beam type, spot diameter, repetition frequency, laser power, scanning speed, number of scans, scanning path, scanning line spacing and scanning area.
2. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: In step 1, the transparent material is transparent glass or transparent ceramic.
3. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The transparent glass described in step 1 is quartz glass, silica glass, glass-ceramics, soda-lime glass, aluminosilicate glass or borosilicate glass.
4. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The transparent ceramic described in step 1 is an oxide transparent ceramic or a non-oxide transparent ceramic.
5. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: In step 1, the oxide transparent ceramic is sapphire, aluminum oxide, magnesium oxide, beryllium oxide, yttrium oxide or spinel.
6. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The non-oxide transparent ceramic in step 1 is gallium arsenide, zinc sulfide, zinc selenide, magnesium fluoride, calcium fluoride or magnesium aluminate.
7. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: In step 1, the polishing method of the graphite surface to be connected is: polishing step by step using 3000-7000 mesh sandpaper; the polishing method of the transparent material is: polishing step by step using 400-7000 mesh sandpaper.
8. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The polishing method of the graphite and the transparent material in step 1 is: using a diamond polishing agent with a particle size of 0.5 to 2.5 μm and polishing for 2 to 20 minutes.
9. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The cleaning method in step 1 is: first rinse the polished surface with acetone or anhydrous ethanol, then ultrasonically clean it in acetone or anhydrous ethanol for 5 to 30 minutes, and finally air dry it.
10. The method for connecting graphite and transparent materials using ultrafast laser according to claim 1, characterized in that: The wavelength in step three is in the infrared band, the pulse width is 1fs to 10ps, the beam type is a Gaussian beam, the spot diameter is 1 to 50μm, the repetition frequency is 1kHz to 1MHz, the laser power is 5mW to 50W, the scanning speed is 0.1 to 10mm / s, the number of scans is 1 to 10, the scanning path is Z-shaped, S-shaped, parallel line-shaped, cross-shaped, concentric rectangle, concentric circle or spiral line-shaped, the scanning line spacing is 10μm to 1mm, and the scanning area is the contact area between graphite and the transparent material.
Citation Information
Patent Citations
Graphite composite and preparation method thereof, and shell of electronic product
CN106564234A
Ceramic nano-crystallization method based on ultrafast laser remelting
CN111393182A
Ultrafast laser stacking manufacturing method of transparent anti-bullet ceramic
CN117362064A
High-efficiency and high-strength ultrafast laser welding method for transparent material
CN117658430A
Joining Polymeric Materials
US20120183748A1